Regulation of otic neurosensory specification by Notch and Wnt signalling: insights from RNA-seq screenings in the embryonic chicken inner ear - Żak, Magdalena; Støle, Thea P.; Plagnol, Vincent; Daudet, Nicolas (Frontiers in Cell and Developmental Biology, 2023)
The Notch and Wnt signalling pathways play key roles in the formation of inner ear sensory organs, but little is known about their transcriptional effectors and targets in this context. Here, we perturbed Notch and Wnt activities in the embryonic chicken otic vesicle using pharmacological treatment or in ovo electroporation of plasmid DNA, and used RNA-Seq to analyse the resulting changes in gene expression. Compared to pharmacological treatments, in ovo electroporation changed the expression of fewer genes, a likely consequence of the variability and mosaicism of transfection. The pharmacological inhibition of Notch activity induced a rapid change in the expression of known effectors of this pathway and genes associated with neurogenesis, consistent with a switch towards an otic neurosensory fate. The Wnt datasets contained many genes associated with a neurosensory biological function, confirming the importance of this pathway for neurosensory specification in the otocyst. Finally, the results of a preliminary gain-of-function screening of selected transcription factors and Wnt signalling components suggest that the endogenous programs of otic neurosensory specification are very robust, and in general unaffected by the overexpression of a single factor.Altogether this work provides new insights into the effectors and candidate targets of the Notch and Wnt pathways in the early developing inner ear and could serve as a useful reference for future functional genomics experiments in the embryonic avian inner ear.